(untitled) (Journal of Parents and Teachers, 2014)
How can a blind man watch a video on Youtube or an image in Flickr? How does a man with cerebral palsy use a mouse? This article presents one of the most ambitious projects for IT resources management in diversity awareness field in Spain to make new technologies accessible to everyone in this society.